Descriptive Study of Neonatal Sepsis in the Post Graduated Hospital Khost Afghanistan - Arifzai, Amanullah; Qadri, Abdullah; Maiwand (Journal for Research in Applied Sciences and Biotechnology, 2023)
Introduction: Since neonatal Sepsis are causes a large number of neonatal hospitalizations and considered one of the most common problems of NICUs worldwide, also a large number of neonatal morbidity and mortality occurs in developing and developed countries. 1.6 million to 4 million deaths occur in the world, 40% of newborns in the first week. Diagnosis of the disease in newborns is determined by the level and equipment of the clinic and is based on the detection of antenatal and postnatal risk factors, respiratory and general symptoms, radiological signs, markers of the systemic inflammatory response syndrome / bacterial infections, and the results of etiological diagnosis. The combination of ampicillin with gentamicin is used for initial therapy of early pneumonia in newborns. In case of late neonatal pneumonia that occurred in a hospital, primary therapy must necessarily include anti pseudomonas and anti-staphylococcal antibiotics. Gram-negative antibiotics are given to treat community-acquired pneumonia in newborns. Research Question: What is the frequency and pattern of neonatal sepsis in Khost provincial specialized hospitals? Methodology: Our research is descriptive type that based on a case series, which took place from the first date of hamal 1400 to the last date of hoot, During this year 2311 patients were hospitalized in Khost post graduate Hospital, 821 patients were newborns, out of these 821 patients, 314 patients were diagnosed neonatal sepsis